Feminist Character Irene Adler in Sherlock Holmes: A Scandal in Bohemia - Chika Azizah Purtanto; Ananda Da'watus Solikhah; Wahyu Indah Mala Rohmana (LPPM Universitas Bina Sarana Informatika, 2024)
The issue of feminism has been a topic of discussion for many years, transforming several fields, including literature. As feminist issues have emerged, many literary works have begun to portray feminist characteristics. One of them is Sir Arthur Conan Doyle's A Scandal in Bohemia, which has the feminist character of Irene Adler. Irene Adler is an interesting central character in this classic Sherlock Holmes story. Sherlock Holmes. Known for her intelligence and independence, Adler is feminist in the detective narrative. Irene Adler's character challenges existing ideas about women in literature at the time. The author used a qualitative method with a feminist literary criticism approach based on the theory of modern feminism, which states that everyone has the right to determine their own path of life, regardless of the influence of their environment. After analyzing the story of A Scandal in Bohemia, the author found seven characters of Irene Adler that represent feminist characters, such as strong-willed, assertive, independent, freedom of expression, self-confidence, strategic intelligence, and the ability to challenge and change stereotypes and male views of women. The implication of this research is that readers can gain a better understanding of how feminist characters contribute to the development of plots and themes in certain literary works or media.